Improving Qur’anic Literacy through the Tartil Method: A Classroom Action Research in Junior High School - Arif Rohman; Ahmad Fahri Yahya Ainuri (FITK UIN Walisongo Semarang, 2026)
This study aims to determine the effectiveness of the Tartil method in improving the mastery of makhraj, tajwid, and fluency in reading the Qur'an of grade IX students of SMP Negeri 1 Jaken. The study used a Classroom Action Research (CAR) approach which was implemented in three cycles. Research data were collected through Qur'an reading ability tests, observation of learning activities, and analysis of student learning outcome documents. The results showed that the gradual application of the Tartil method was able to significantly improve students' Qur'an reading ability from pre-cycle to cycle III. In the pre-cycle, student learning completeness only reached 27% with an average score of 61.5. After the application of the Tartil method in cycle I, completeness increased to 50% with an average score of 70.2. In cycle II it increased to 67% with an average score of 77.8, and in cycle III it reached 93% with an average score of 85.6. Mastery of pronunciation increased from 40% to 90%, while mastery of tajweed increased from 35% to 88%. Reading errors that affect meaning also decreased from 40% to 8%. In addition to cognitive and psychomotor aspects, the Tartil method also increased student learning motivation from 45% to 88% and self-confidence from 40% to 80%. These findings indicate that gradual practice, teacher feedback, the use of audio-visual media, and collaborative learning are effective in improving the quality of Quranic reading learning. An important contribution of this research is providing a systematic and sustainable Tartil learning model to improve students' Quranic literacy in Islamic religious education-based schools. Keywords: Qur'anic Literacy, Tartil Method, Classroom Action Research, Junior High School